Power-sharing in the Ukrainian executive authorities - Movchan, U. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article is considered the main theories of government in plural society. It has been shown that Lijphart’s consociational democracy is the optimal model of democracy for Ukraine. Also the article is analyzed the shortcomings of Ukrainian political system. Democracy’s indexes show that the presence of two main parties inside the Cabinet of Ministers is favorable for democracy.